Both A and C would be solutions to the equation.
In order to solve for this you must first get the equation equal to 0.
2x^2+5x+8=6 ----> subtract 6 from both sides
2x^2 + 5x + 2 = 0
Now knowing this we can use the coefficients of each one in descending order of power as a, b and c.
a = 2 (because it is the coefficient to x^2)
b = 5 (because it is the coefficient to x)
c = 2 (because it is the end number)
Now we can plug these values into the quadratic equation.
![\frac{-b +/- \sqrt{b^{2} - 4ac } }{2a}](https://tex.z-dn.net/?f=%20%5Cfrac%7B-b%20%2B%2F-%20%5Csqrt%7Bb%5E%7B2%7D%20-%204ac%20%7D%20%7D%7B2a%7D%20)
![\frac{-5 +/- \sqrt{5^{2} - 4(2)(2) } }{2(2)}](https://tex.z-dn.net/?f=%20%5Cfrac%7B-5%20%2B%2F-%20%5Csqrt%7B5%5E%7B2%7D%20-%204%282%29%282%29%20%7D%20%7D%7B2%282%29%7D%20)
![\frac{-5 +/- \sqrt{9} }{4}](https://tex.z-dn.net/?f=%20%5Cfrac%7B-5%20%2B%2F-%20%5Csqrt%7B9%7D%20%7D%7B4%7D%20)
![\frac{-5 +/- 3 }{4}](https://tex.z-dn.net/?f=%20%5Cfrac%7B-5%20%2B%2F-%203%20%7D%7B4%7D%20)
![\frac{-5 + 3 }{4}](https://tex.z-dn.net/?f=%20%5Cfrac%7B-5%20%2B%203%20%7D%7B4%7D%20)
or -1/2 for the first answer
![\frac{-5 - 3 }{4}](https://tex.z-dn.net/?f=%20%5Cfrac%7B-5%20-%203%20%7D%7B4%7D%20)
or -2 for the second answer
The picture is super blurry so i can’t see anything
Answer:
No, you could write the formula different but not change it
Step-by-step explanation:
Answer:
1/2
Step-by-step explanation:
5 / 10 = 1/2
Answer:
It should be 42.25 instead
Step-by-step explanation: